Peritoneal Effusion in a Dog due to Babesia gibsoni Infection - Suresh Gonde; Sushma Chhabra; L. D. Singla; B. K. Bansal (Case Reports in Veterinary Medicine)
A five-year-old male Labrador was presented to Teaching Veterinary Clinics of GADVASU with a primary complaint of distended abdomen, fever, and anorexia. The dog was found to be dull with elevated rectal temperature (104°F), heart rate (148 per minute), and respiration rate (58 per minute). Blood smear examination and PCR assay revealed that dog was positive for Babesia gibsoni. Elevated bilirubin, alanine amino transferase (ALT), alkaline phosphatase (ALP), creatinine, blood urea nitrogen (BUN), total leucocyte count, hypoalbuminaemia, and hypoproteinaemia were haematobiochemical alterations. Radiography and ultrasonography showed ground glass appearance and anechoic area of abdomen, respectively.